2018
DOI: 10.2139/ssrn.3158510
|View full text |Cite
|
Sign up to set email alerts
|

Competition in Dual Markets: Implications for Banking System Stability

Abstract: This paper examines the impact of market competition on the stability of Islamic and conventional banks in countries where these banks operate alongside one another. To investigate this issue, we use a sample of 100 Islamic and 390 conventional banks from 19 countries. Our baseline result shows that competition in a dual market erodes banks' stability.The heightened competitive pressure in a dual market encourages banks to engage in excessive risk-taking that can jeopardize their stability. However, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
3
8
0
1
Order By: Relevance
“…This is in line with the literature on banks' risk taking where more risk-taking makes banks less stable and increased chances of default. This is also in line with the literature on competition and banking stability where Lerner, the measure of market power, is used as an inverse measure of competition and a positive relationship is found thus competition-fragility view is supported, implying that more market power makes banks more stable (Jiménez et al, 2013;Alfauzan and Tarchouna, 2017;Kabir and Worthington, 2017;Leroy and Lucotte, 2017;Danisman and Demirel, 2018;Risfandy et al, 2018).…”
Section: Regression Resultssupporting
confidence: 86%
“…This is in line with the literature on banks' risk taking where more risk-taking makes banks less stable and increased chances of default. This is also in line with the literature on competition and banking stability where Lerner, the measure of market power, is used as an inverse measure of competition and a positive relationship is found thus competition-fragility view is supported, implying that more market power makes banks more stable (Jiménez et al, 2013;Alfauzan and Tarchouna, 2017;Kabir and Worthington, 2017;Leroy and Lucotte, 2017;Danisman and Demirel, 2018;Risfandy et al, 2018).…”
Section: Regression Resultssupporting
confidence: 86%
“…Using a dataset of 14 full-fledged Islamic banks and 19 Islamic windows banks in Indonesia from 2013 to 2018, it was found that the full-fledged Islamic banks were less stable than Islamic ones. This result signals that the Islamic banking market is highly competitive, as suggested by some studies (Meslier, Risfandy, & Tarazi, 2017;Risfandy, Tarazi, & Trinugroho, 2020). This result enriches the literature in Islamic banks, particularly in comparing Islamic banks and Islamic windows, showing that the latter has better stability than the former.…”
Section: Introductionsupporting
confidence: 72%
“…The stability measures used in this study were the z-Score and Non-Performing Loans (NPL), which have been extensively employed in the literature (Abedifar et al, 2013;Beck et al, 2013;Čihák & Hesse, 2010;Hassan et al, 2019;Ibrahim & Rizvi, 2017;Kabir et al, 2015). While the NPL could be a proxy to measure asset quality, it could also measure bank stability along with the z-score (Risfandy et al, 2020). The ability of the zscore to identify risks, both across periods and during the crisis (2008)(2009)(2010)(2011), is at least as good as the CAMELS, but the Z-Score requires fewer data, and the z-score proves to be more effective when the bank business may be more sophisticated as is the case for large and commercial banks (Chiaramonte, Croci, & Poli, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…banks. Alam et al (2019); Kabir and Worthington (2017) and Risfandy et al (2018) find that competition raises the fragility of banks in a dual banking system. However, Fu et al (2014) finds that competition makes the banking system in 14 Asia Pacific economies more stable.…”
Section: Literature Reviewmentioning
confidence: 99%